The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1111/adb.12303
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic regulation of nociceptin/orphanin FQ and corticotropin-releasing factor system genes in frustration stress-induced binge-like palatable food consumption

Abstract: Evidence suggests that binge eating may be caused by a unique interaction between dieting and stress. We developed a binge-eating model in which female rats with a history of intermittent food restriction show binge-like palatable food consumption after a 15-minute exposure to the sight of the palatable food (frustration stress). The aim of the present study was to investigate the regulation of the stress neurohormone corticotropin-releasing factor (CRF) system and of the nociceptin/orphanin FQ (N/OFQ) system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
30
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 91 publications
7
30
0
Order By: Relevance
“…3.1 | Binge-eating behavior in rats exposed to food restriction and binge-eating test As reported in previous studies Micioni Di Bonaventura et al, 2014;Pucci et al, 2016), we found that rats lose weight during the food restriction period but they regain it during the subsequent free-food period. On the last day of the BE FIGURE 2 Schematic representation of the rat faah gene and the 5 0 upstream region.…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…3.1 | Binge-eating behavior in rats exposed to food restriction and binge-eating test As reported in previous studies Micioni Di Bonaventura et al, 2014;Pucci et al, 2016), we found that rats lose weight during the food restriction period but they regain it during the subsequent free-food period. On the last day of the BE FIGURE 2 Schematic representation of the rat faah gene and the 5 0 upstream region.…”
Section: Resultssupporting
confidence: 78%
“…In this work, the combination of stress and repeated food restriction induced binge-eating behavior for highly palatable food in female rats as shown previously (Cifani et al, 2009;Piccoli et al, 2012), where regulation of nociceptin/orphanin FQ and corticotropin-releasing factor genes was reported as a potential contributor Pucci et al, 2016). Here, we extended our previous investigations to the role of ECS gene regulation in the same animal model.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Cifani et al, 2010; C. Cifani et al, 2009; Micioni Di Bonaventura, Cifani, et al, 2012; Micioni Di Bonaventura, Vitale, et al, 2012; Pucci et al, 2015), body weight of rats was reduced during the 4 days of food restriction, but immediately afterwards the animals increased their food intake and rapidly recovered their body weight to levels of controls by the end of each cycle. On the test day body weight of animals, as well as their food intake in the previous 24 h, were not significantly different among the groups (data not shown).…”
Section: Resultsmentioning
confidence: 95%
“…A recent systematic review (Torensma et al, 2016) included two studies suggesting that obese subjects have a lower pain threshold than nonobese subjects (Pradalier et al, 1981;McKendall and Haier, 1983), but four studies indicating that obese subjects have a higher one (Zahorska-Markiewicz et al, 1988;Miscio et al, 2005;Maffiuletti et al, 2011;Dodet et al, 2013). Other findings concluded that body mass index and body fat may influence the pain threshold (Bohnert et al, 2013;Price et al, 2013;Tashani et al, 2017;Torensma et al, 2017), and the intensity of the perception of stimuli changes proportionally with the levels of subcutaneous fat in the affected body area. Price et al (2013) reported that obese people have a higher pain threshold in the abdominal area compared to the hands and forearms.…”
Section: Introductionmentioning
confidence: 99%